If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3+6m=42
We move all terms to the left:
3+6m-(42)=0
We add all the numbers together, and all the variables
6m-39=0
We move all terms containing m to the left, all other terms to the right
6m=39
m=39/6
m=6+1/2
| (2y)(3y)=3 | | 4=-2/5c | | 7^((-2x^2)-6)=(1/343)^(6x-10) | | 5(4x-1.5)=4x-2 | | 5m+55=290 | | 0.75y-2y=5 | | 3x+4=2x+6X=2 | | 8(a-8)=120 | | -5x+31(1-2x)=-52 | | 3.2w-0.3=1.3 | | 7(b-5)=21 | | t.7/10=7/10 | | r.5=5.5 | | (5)/(3x-2)=(4)/(x-3) | | 6/5x+2/3=-11 | | (102/100)^2n=2 | | 2-5x=1/5(25-40x) | | -3x+8=15-4x | | r/9.5=1 | | x/4+14=42 | | (102/100)2n=2 | | r÷9.5=1 | | 2+5/3b+11−18=20 | | 4(x+7)=5x+8x= | | 4x-(3x-6)=1 | | 1.05x=45,000 | | 2.4=19.8/x | | -3(2g+6)+g=2 | | 3y–48=2y–26 | | X+3/2+x-2/4=3/6 | | 5/3x=2x+10/3x5/3x | | 2-1.5d=0.5 |